(untitled) (Global Scientific Review, 2024)
Efforts to increase online media traffic can be realized by increasing reader engagement. The high frequency and intensity of readers and interactions in reading news online, such as commenting and sharing the article, indicate a high level of reader involvement. The article attempts to show the influence between the motives of using online media, news selection, and news attractiveness on the level of reader involvement. Through distributing questionnaires to 95 students, the study uses a survey method with an explanative quantitative approach. Data are analyzed using multivariate analysis techniques with correlation coefficient test and multiple linear regression. The results show a strong and positive correlation between the motive for media use, news selection, the level of media attractiveness, and the level of reader involvement of 0.659. The multiple linear regression test also proves a significant influence between the three independent variables on the level of reader involvement with an influential contribution of 43.4%